Spin Polarization and Exchange Interaction in a Diluted Magnetic Qunautm Dot - A. John Peter; K. Lily Mary Eucharista (Advances in Condensed Matter Physics)
The spin interaction energy of different Mn2+ ions with and without an itinerant electron is evaluated for different dot radii. Magnetization is calculated for various concentrations of Mn2+ ions with different dot sizes. Spin polaronic shifts are estimated using a mean field theory. The lowest binding energies of electrons in a Cd1-xMnxTe quantum dot are also calculated. Results are obtained for Cd1−xinMnxinTe/Cd1−xoutMnxoutTe structures as a function of the dot radius variationally. It is found that (i) more number of Mn2+ spins enhance the spin polaronic effect and it varies linearly with the concentration, (ii) spin polarization of Mn2+ ions increases with the concentration for any dot radii, (iii) the magnetization of Mn subsystem increases with the concentration of Mn2+ ions and this feature is predominant for smaller dots, and (iv) variation of increase in ionization energy is sharper for smaller dots with increase in concentration. These results are discussed with the available data in literature.